2021
DOI: 10.1177/10556656211021700
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Delayed Primary Cleft Surgery and Unrepaired Cleft Lip and/or Palate in 5 UK Cleft Centers

Abstract: Background: There may be many reasons for delays to primary cleft surgery. Our aim was to investigate the age of children undergoing primary cleft lip or primary cleft palate repair in 5 cleft centers within the United Kingdom. Identify the reasons for delayed primary cleft lip repair (beyond 6 months) and delayed primary palate repair (beyond 13 months). Identify children who had a cleft lip and/or palate (CL±P) that was intentionally unrepaired and the reasons for this. Methods: A retrospective, multicenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These restrictions therefore presented a significant challenge for speech-language pathology (Britton, 2021). It is worth noting that delays in the U.K. cleft treatment pathway are not unique to the pandemic and were present beforehand, most commonly when children had comorbidities (Butterworth et al, 2021). The magnitude of effect that the pandemic has had on U.K. cleft care delays is not yet fully known; however, delays to the multidisciplinary pathway are likely to be more numerous and widespread than prior to the pandemic.…”
Section: Provision Of Cleft Services Including Speech-language Pathology During the Pandemicmentioning
confidence: 99%
“…These restrictions therefore presented a significant challenge for speech-language pathology (Britton, 2021). It is worth noting that delays in the U.K. cleft treatment pathway are not unique to the pandemic and were present beforehand, most commonly when children had comorbidities (Butterworth et al, 2021). The magnitude of effect that the pandemic has had on U.K. cleft care delays is not yet fully known; however, delays to the multidisciplinary pathway are likely to be more numerous and widespread than prior to the pandemic.…”
Section: Provision Of Cleft Services Including Speech-language Pathology During the Pandemicmentioning
confidence: 99%
“…The timing of cleft lip reconstruction (IQR: 4 to 5 months) and soft palate reconstruction (IQR: 8 to 12 months) is similar to previous UK reports 10,38,39 and does not appear to have altered with centralization of care over the last 3 decades. Where primary reconstruction was delayed beyond the NHS threshold ages, the SSF data could not elucidate the reason, but has been reported elsewhere to occur more commonly in children with co-morbidities 40 . We would hope the baseline data from this study in conjunction with outcome data that is being collected will contribute to the debate around optimal timing for palatal surgery in relation to critical speech development 41 psychological and growth outcomes 42,43 .…”
Section: Timingmentioning
confidence: 92%
“…Repair is undertaken between the age of 3 and 6 months in line with accepted guidance in the United Kingdom. 7 All measurements in this study were undertaken by the three consultant specialist cleft surgeons working in the nationally commissioned cleft service for Scotland according to an agreed technique. Pre-study, the three senior authors technique was observed by the corresponding first author who confirmed that technique and points of reference were the same for all surgeons.…”
Section: Methodsmentioning
confidence: 99%